2018
DOI: 10.1016/j.celrep.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

PKCε Inhibits Neuronal Dendritic Spine Development through Dual Phosphorylation of Ephexin5

Abstract: SUMMARY Protein kinase C (PKC)-dependent mechanisms promote synaptic function in the mature brain. However, the roles of PKC signaling during synapse development remain largely unknown. Investigating each brain-enriched PKC isoform in early neuronal development, we show that PKCε acutely and specifically reduces the number of dendritic spines, sites of eventual synapse formation on developing dendrites. This PKCε-mediated spine suppression is temporally restricted to immature neurons and mediated through the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…(ARHGEF5/TIM1), Ephexin4 (ARH GEF16), and Ephexin5 (ARHGEF15/Vsm-RhoGEF) 9,21,[29][30][31][32] . It has been reported that Ephexin1 and Ephexin5 are phosphorylated by Src or Eph receptors but not ARH-GEF16 21,29,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ARHGEF5/TIM1), Ephexin4 (ARH GEF16), and Ephexin5 (ARHGEF15/Vsm-RhoGEF) 9,21,[29][30][31][32] . It has been reported that Ephexin1 and Ephexin5 are phosphorylated by Src or Eph receptors but not ARH-GEF16 21,29,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The Ephexin subfamily comprises five members: Ephexin1 (ARHGEF27/ NGEF), Ephexin2 (ARHGEF19/WGEF), Ephexin3 (ARHGEF5/TIM1), Ephexin4 (ARHGEF16), and Ephexin5 (ARHGEF15/Vsm-RhoGEF) 9 , 21 , 29 32 . It has been reported that Ephexin1 and Ephexin5 are phosphorylated by Src or Eph receptors but not ARHGEF16 21 , 29 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study with hippocampal slices from mice showed that protein kinase C (PKC) delta increases, whereas PKC epsilon decreases, sensitivity of IPSCs to acute ethanol (80 mM) exposure (including duration of ethanol’s potentiation) 54 . These PKC isoforms have been demonstrated to be expressed in the hippocampus of P6 mice 55 . Future studies should determine whether the relative activity levels of these kinases in vicinity of GABA A receptors modulate their sensitivity to ethanol during early postnatal development.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps changes in the expression of these proteins might be responsible for the correct distribution of PSD-95. In this respect, it has been described that PKC isoforms acting through GEFs (Guanine nucleotide exchange factors which are activators of small GTPases) are able to modulate dendrite spine morphology (Schaffer et al, 2018). For example, PKCγ, the main PKC isoform involved in the morphological changes mediated by CD40L reverse signaling in MSNs (Carriba and Davies, 2017), phosphorylates βPIX (Pakinteracting exchange factor-β), a GEF protein that regulates Cdc42/Rac1 signaling (Shirafuji et al, 2014).…”
Section: Differences In the Expression Of Rhomentioning
confidence: 99%